Seeking deviations from South Africaﾒs tax treaty policy with respect to treaties in Africa: evidence from the treaty practice - de Wet, Mary-Ann (Department of Finance and Tax, 2020)
Since South Africa was welcomed back into the international arena in 1994, there has been a significant increase in the number of tax treaties concluded between South Africa and other Sub-Saharan Africa countries, as part of South Africa’s goal to expand into Sub-Saharan Africa (SSA). The purpose of this dissertation is to determine whether these treaties concluded between South Africa and SSA countries have been influenced by South Africa’s stated tax treaty policy, or have been guided by regional practices or to confirm whether South Africa’s tax treaty practices have influenced any regional models. This dissertation includes a detailed analysis of 18 tax treaties concluded between South Africa and other SSA countries. This analysis is used to identify any significant deviations in these treaties as compared to the OECD Model and the UN Model. The SSA region has several economic organisations that have developed tax models to cater for treaty negotiations of developing countries. These models include the African Tax Administration Forum (ATAF) Model, the Southern Africa Development Community (SADC) Model and the East African Community (EAC) tax agreement. The study observes that South Africa’s tax treaty practise generally follows the OECD Model, but also incorporates certain provisions of the UN Model. The analysis of the 18 treaties as compared to the OECD Model identified 31 significant deviations to the OECD Model, and of these deviations, 22 (71%) align to the provisions of the UN Model. These significant deviations were analysed to determine if they arose from South Africa’s stated positions on the OECD Model, influenced by South Africa’s domestic laws, or arose at the insistence of the other Contracting State, or from other factors. v The findings suggest that of the 31 deviations, the majority (80%) arise out of South Africa’s positions on the OECD Model and from its domestic laws. Further analysis was conducted to determine if these significant deviations were contained in the SSA regional tax models. The findings indicate that the SADC Model has the highest correlation as it includes 87% of these deviations, followed by ATAF (77%) and EAC (71%). An additional analysis, by country per regional body, was conducted on the deviations arising from South Africa’s treaty practices. This analysis indicates that 80% of South Africa’s treaty practices occur in the ATAF Model, 84% in the SADC Model, and 72% in the EAC Model. This analysis found that, on average, 82% of treaties concluded with ATAF member countries, 81% of SADC member countries and 89% of EAC member countries aligned to South Africa’s treaty practices. The high correlation to the SADC and ATAF Models indicates that South Africa’s tax treaty practices have influenced the development of these regional models, and the high correlation between the treaties for each country and region, suggests that the majority of the treaties have been significantly influenced by South Africa’s tax treaty practices. Thus, the conclusion is that the majority of the significant deviations found in South African treaties concluded with Sub-Saharan African countries arise from the South African tax treaty practices which are generally based on the OECD model, with the inclusion of certain provisions of the UN Model. These deviations align with South Africa’s position to the OECD Model and its domestic laws, which form the South African treaty practices. It is concluded that these treaty practices have significantly guided the SSA treaties and suggests that these treaty practices have influenced the Sub-Saharan African ATAF and SADC Models.